SURVEI TOXOPLASMOSIS PADA TIKUS DI DESA SUMBERAGUNG BANTUL DENGAN UJI SEROLOGI AGLUTINASI LANGSUNG (TOXO-SCREEN DA) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Epidemiologic problems of toxoplasmosis am very complicated, because so many domestic animals are eflicient reservoirs of human infection. Cattle, pigs, goats, sheeps, cats are susceptible and may show a high infection rate in certain areas. The purpose of this study was to determine the frequencies of rats in Sumberagung, Bantu I. A serological test by toxo-screen direct aglutination for IgG detection on rats has been carried out. The results indicated that 11.90% of rats were positive for toxoplasma specific IgG antibodies. It was suggested too that there were no difference between the frequencies of toxoplasmosis on female and male rats and between Rattus ratus tiomanicus and Rattus ratus diardi.